2023
DOI: 10.1101/2023.02.22.529538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The AEGEAN-169 clade of bacterioplankton is synonymous with SAR11 subclade V (HIMB59) and metabolically distinct

Abstract: Bacterioplankton of the SAR11 clade are the most abundant marine microorganisms and consist of numerous subclades spanning Order level divergence (Pelagibacterales). The assignment of the earliest diverging subclade V (a.k.a. HIMB59) to thePelagibacteralesis highly controversial, with multiple recent phylogenetic studies placing them completely separate from SAR11. Other than through phylogenomics, subclade V has not received detailed examination due to limited genomes from this group. Here, we assessed the ec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 103 publications
(178 reference statements)
1
2
0
Order By: Relevance
“…When analyzed by taxonomic order, we found that the most sensitive taxa to substrate limitation across all compound classes were the Pelagibacterales (24.9% of models showed substantial growth reduction to at least one compound class), SAR86 (21.6% showed substantial growth reduction), and AEGEAN-169 (19.1% showed substantial growth reduction) (Supplemental Figure S5a). This is consistent with these groups being classically oligotrophic organisms with streamlined genomes and limited metabolic flexibility 1719 . By contrast, the classically copiotrophic groups (the Enterobacterales , Sphingomonadales , and Rhodobacterales ) showed the least growth sensitivity to substrate reduction, with only 5.9%, 9.1% and 9.4% of these models showing substantial growth reduction across all compound classes, respectively (Supplemental Figure S5a).…”
Section: Resultssupporting
confidence: 86%
“…When analyzed by taxonomic order, we found that the most sensitive taxa to substrate limitation across all compound classes were the Pelagibacterales (24.9% of models showed substantial growth reduction to at least one compound class), SAR86 (21.6% showed substantial growth reduction), and AEGEAN-169 (19.1% showed substantial growth reduction) (Supplemental Figure S5a). This is consistent with these groups being classically oligotrophic organisms with streamlined genomes and limited metabolic flexibility 1719 . By contrast, the classically copiotrophic groups (the Enterobacterales , Sphingomonadales , and Rhodobacterales ) showed the least growth sensitivity to substrate reduction, with only 5.9%, 9.1% and 9.4% of these models showing substantial growth reduction across all compound classes, respectively (Supplemental Figure S5a).…”
Section: Resultssupporting
confidence: 86%
“…S5, S7). This contrasts with other abundant free-living microorganisms like SAR11 and Aegean-169 which both have subclades adapted to lower salinities [70,82]. Other Roseobacter relatives have been isolated from brackish salinities as well [18,19,83,84], and CHAB-I-5 members have been observed in equivalent abundances along the salinity gradient of the Chesapeake Bay [14].…”
Section: Discussionmentioning
confidence: 87%
“…Nitrosomonas (ammonia oxidizers) and LS‐NOB (nitrite oxidizers) might perform shared denitrification (Lehtovirta‐Morley, 2018), although probably less effective than ammonia oxidation by archaea (Rasmussen & Francis, 2022). AEGEAN‐169 (recently designated as SAR11 clade V) can potentially utilize a broader range of CHOs than other SAR11 clades, and might participate in trace metal cycling and thiamin synthesis (Getz et al, 2023).…”
Section: Resultsmentioning
confidence: 99%